2009
DOI: 10.1111/j.1742-1241.2008.01910.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal obesity: a review of interventions

Abstract: This study finds that there is a deficiency of appropriately designed interventions for maternal obesity and it concludes by highlighting areas for developing a more effective strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
75
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 61 publications
2
75
0
1
Order By: Relevance
“…A recent Cochrane review found no difference between exercisers and non-exercisers 12 . This is in agreement with the systematic reviews of Siega-Riz et al 13 and Birdsall 14 , both concluding that few studies examined exercise as a determinant of maternal weight gain. These authors emphasised the need for high quality RCTs in this area.…”
Section: Introductionsupporting
confidence: 79%
“…A recent Cochrane review found no difference between exercisers and non-exercisers 12 . This is in agreement with the systematic reviews of Siega-Riz et al 13 and Birdsall 14 , both concluding that few studies examined exercise as a determinant of maternal weight gain. These authors emphasised the need for high quality RCTs in this area.…”
Section: Introductionsupporting
confidence: 79%
“…Janney et al found inverse associations between breast-feeding and PPWR, yet the authors concluded that the effect of lactation on PPWR was small and that promoting breast-feeding was not relevant in order to minimize PPWR (15) . Maternal obesity is a complex interplay between a number of factors and Birdsall et al concluded in a review article on interventions on maternal obesity that there is a deficiency of appropriately designed interventions in this field (12) . In the present study an inverse association between duration of full and partial breast-feeding and maternal PPWR was found at 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies for reducing the risk of PPWR often include modification of lifestyle factors like diet and physical activity (11,12) . Breast-feeding also is usually suggested as a means for women to reduce PPWR.…”
mentioning
confidence: 99%
“…According to WHO, the prevalence of obesity in pregnancy ranges from 1.8 to 25.3%. 1 Obesity before and during pregnancy constitutes a major risk factor for both maternal and fetal complications, 2,3 while it has been shown that offspring of obese women have a higher likelihood of becoming obese during childhood and of developing metabolic syndrome in adulthood ( Figure 1). 4 Pregnancy is a period during which obesity can be relatively effectively confronted as the mother is more disposed to accept lifestyle modifications, such as balanced diet and physical exercise, which will most likely improve fetal health.…”
Section: Introductionmentioning
confidence: 99%
“…4 Pregnancy is a period during which obesity can be relatively effectively confronted as the mother is more disposed to accept lifestyle modifications, such as balanced diet and physical exercise, which will most likely improve fetal health. 2 The control of body weight during this period is of paramount importance for delivery outcome as well as maternal and neonatal health. In the present communication, data on the effects of obesity prior to and during pregnancy on the health status of mother and fetus will be reviewed.…”
Section: Introductionmentioning
confidence: 99%